Analysis Grounding System as Building Equipment Security Udayana University Denpasar - Janardana, I G. N.; Wijaya, W. Arta; Partha, Cok Gede Indra; Budiastra, N. (Journal of Electrical, Electronics and Informatics; Vol 1 No 2 (2017): JEEI (September 2017), 2017)
Grounding system is one of the components in building equipment security. To fulfill the operational continuity of electronic equipment in Faculty of Engineering, Udayana University, Denpasar, a grounding system with a ground resistance of ? 3 ohms is required to be installed. The aim of this study is to find out the characteristics of grounding system to secure the equipment in the building around the research location, with ground resistance of ? 3 ohms and it is expected to be beneficial to use as a reference in grounding system installation as well as.  According to the measurement results at the research location, it is found that the soil resistance value is equal to 0.23 ohms, where the soil resistivity (?) is 28.89 Ohm-meters. There are some results analysis obtained in ground resistance value of ? 3 Ohm. Those are 1) grounding system type 1 rod where minimal depth installation of the electrode is 14 meters with ground resistance value of 2.6751 ohms; 2) grounding system type two rod with s < L, it is obtained that each depth is 8 meters with distance of 2 meters between electrodes, where the ground resistance value is 2.4940 ohms. In the installation of two electrodes with s > L, it is gained that the depth of each electrode is 6 meters where the distance between the electrodes is 8 meters and the ground resistance value is 2.8718 ohms. By applying the plates type grounding system with 3 meters in length, 1 meter in width, and 2 meters in installation depth is gained 2.8431 ohms ground resistance value. Furthermore, by applying grid type grounding system with 2 meters in length h = 2,5 meters in depth, A = 4 meters in width and the total length of the electrode diameter 1 cm is 504 meters, it is obtained 2.0978 ohms ground resistance value.